2015
DOI: 10.1001/jamainternmed.2014.7774
|View full text |Cite
|
Sign up to set email alerts
|

Research Misconduct Identified by the US Food and Drug Administration

Abstract: IMPORTANCE Every year, the US Food and Drug Administration (FDA) inspects several hundred clinical sites performing biomedical research on human participants and occasionally finds evidence of substantial departures from good clinical practice and research misconduct. However, the FDA has no systematic method of communicating these findings to the scientific community, leaving open the possibility that research misconduct detected by a government agency goes unremarked in the peer-reviewed literature.OBJECTIVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…The US Food and Drug Administration (FDA) reports some metrics that are related to the frequency of clinical investigator-related deficiencies, which show that almost 10% of trials they monitored suffer from consent collection issues, such as failure to re-consent when new information becomes available, use of expired forms or non-validated, unapproved forms, consent document not signed or not dated, missing pages in consent document provided to participants, failure to obtain written informed consent, parental permission obtained after child assent, changes made to the consent documents by hand and without IRB approval 3, 4 ( http://www.fda.gov/downloads/AboutFDA/CentersOffices/CDER/UCM256376.pdf; http://www.yale.edu/hrpp/education/documents/CommonProblemsinInformedConsent_2013_vF.pptx). The study by Seife 5 analysed hundreds of clinical trial FDA inspection documents, covering the 1998–2013 period, and showed that a substantial number of them presented evidence of research misconduct, among which 53% were related to failure to protect the safety of patients and/or issues with oversight or informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…The US Food and Drug Administration (FDA) reports some metrics that are related to the frequency of clinical investigator-related deficiencies, which show that almost 10% of trials they monitored suffer from consent collection issues, such as failure to re-consent when new information becomes available, use of expired forms or non-validated, unapproved forms, consent document not signed or not dated, missing pages in consent document provided to participants, failure to obtain written informed consent, parental permission obtained after child assent, changes made to the consent documents by hand and without IRB approval 3, 4 ( http://www.fda.gov/downloads/AboutFDA/CentersOffices/CDER/UCM256376.pdf; http://www.yale.edu/hrpp/education/documents/CommonProblemsinInformedConsent_2013_vF.pptx). The study by Seife 5 analysed hundreds of clinical trial FDA inspection documents, covering the 1998–2013 period, and showed that a substantial number of them presented evidence of research misconduct, among which 53% were related to failure to protect the safety of patients and/or issues with oversight or informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it included meta-analyses of the same all very similar research question. Furthermore, the fabrication of data was uncovered exclusively in a single Chinese clinical site and, once all Chinese data was excluded, the trial yielded statistically significant positive results [16]. Therefore, the average distorting effect that retractions exert on the scientific literature remains to be assessed.…”
Section: Bodymentioning
confidence: 99%
“…This goes hand-in-hand with co-authors verifying results, but this is done by a researcher not directly affiliated with the research project. Auditing data is common practice in research that is subject to governmental oversight, for instance drug trials that are audited by the Food and Drug Administration (Seife 2015).…”
Section: How Can It Be Prevented?mentioning
confidence: 99%